From transgressors to authors: promoting EFL writing through academic integrity integrated instruction - Çelik, Özgür; Razı, Salim (System (Linköping), 2023)
The relationship between academic integrity and plagiarism has been shaped by two governing pedagogies. The first one stipulates imposing sanctions on students who plagiarise. In this case, students are seen as moral slackers, habituated to cheating. The second pedagogy approaches plagiarism as a matter of intertextual issue and highlights the importance of teaching the ethics of intertextual writing through developing pedagogies that offer positive practices. In this approach, students are seen as authors, not transgressors. This study aimed to investigate the effectiveness of a writing instruction, which emphasizes the importance of teaching mechanical, ethical, and rhetorical intertextuality skills along with its role in mitigating plagiarism incidents and enhancing the EFL writing development of secondary school students. A mixed-method time series design was employed to collect data, and the results indicate that teaching intertextuality skills was effective in reducing plagiarism incidents in student papers and enhancing the content, organisation, style, and expression domains in their papers. Such an implementation makes it evident that in approaching student writing in general, plagiarism in particular, we need to shift our writing pedagogy from policing students to engaging them.